2012
DOI: 10.1186/1756-0500-5-308
|View full text |Cite
|
Sign up to set email alerts
|

LEPR c.668A>G polymorphism in a cohort of Sri Lankan women with pre-eclampsia / pregnancy induced hypertension: a case control study

Abstract: BackgroundLeptin is known to be elevated in pre-eclampsia/ pregnancy induced hypertension (PE/PIH). However the reports on the association of leptin receptor (LEPR) c.668A>G polymorphism with PE/PIH are inconsistent.FindingsLEPR c.668A>G polymorphism was studied in a cohort of women with PE/PIH (N = 61) and normotensive pregnancies (N = 40) by polymerase chain reaction / restriction fragment length polymorphism. Genotype and allele frequencies were in Hardy-Weinberg equilibrium within both groups (Chi square t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Our finding was in accordance with the findings of Rigo et al in a study of pregnant Hungarian women [18]. However, several other studies showed no association between c.668A>G and preeclampsia [20,21,34,35]. In this study, the frequency of the minor G allele, whether it was the AG or GG genotype, was significantly associated with the development of preeclampsia.…”
Section: Discussionsupporting
confidence: 93%
“…Our finding was in accordance with the findings of Rigo et al in a study of pregnant Hungarian women [18]. However, several other studies showed no association between c.668A>G and preeclampsia [20,21,34,35]. In this study, the frequency of the minor G allele, whether it was the AG or GG genotype, was significantly associated with the development of preeclampsia.…”
Section: Discussionsupporting
confidence: 93%
“…They reported a greater frequency of the R allele for SNPs K109R (c.326A>G, rs1137100) and Q223R (c.668A>G, rs1137101) of the leptin receptor among Asians when compared to Caucasians. In a recent study by our group [37] the frequency of the R allele for Q223R SNP observed among Sri Lankans was within the range of frequencies reported for Caucasians in the meta-analysis. SLR is generated either by alternative splicing of leptin receptor mRNA or by shedding the ectodomain of membrane-bound receptor protein, thus its levels are unlikely to be affected by SNPs of the leptin receptor or their ethnic variations.…”
Section: Discussionmentioning
confidence: 98%
“…Lastly, one can hypothesize that adipokine signaling (more precisely, the AdipoR and ObR adipokine receptors for adiponectin and leptin, respectively) is altered in women with RPL. Indeed, it has already been reported that certain AdipoR and ObR polymorphisms are associated with reproductive traits or certain reproductive pathologies (such as pre‐eclampsia, and hemolysis, elevated liver enzyme levels and low platelet levels syndrome) …”
Section: Discussionmentioning
confidence: 99%